Factors Influencing Trust in Geothermal Energy Projects: Case of Seven Projects in East-Africa - Mahamoud Abdi, Abdek; Murayama, Takehiko; Nishikizawa, Shigeo; Suwanteep, Kultip (International Journal of Sustainable Energy Planning and Management, 2025)
Geothermal energy is widely considered a clean and renewable energy source, yet it faces significant social opposition in several countries, including Japan, Kenya, Greece, and Switzerland, among others. These challenges are often linked to trust issues. East African countries are actively developing their geothermal energy resources; however, some projects, such as the Olkaria IV and Akiira geothermal energy projects in Kenya, have faced social resistance. This study investigates the factors influencing trust in geothermal energy projects by analyzing public participation materials included in the Environmental and Social Impact Assessment (ESIA) reports of seven geothermal projects in the East African region. Firstly, 150 comments related to trust were selected from a total of 680 comments in the public participation materials. Secondly, a two-step qualitative inductive coding approach was employed to develop four trust categories and fifteen issue-related codes. Finally, dummy variables were created using SPSS 24, and statistical analyses, including correlation and chi-square tests, were conducted. The findings indicate that trust issues predominantly concern corporate trust (34.67%), technological trust (33.33%), and procedural trust (28.67%). Correlation and chi-square analyses revealed that these concerns are linked to employment, corporate support (e.g., corporate social responsibility projects), environmental and social risks, and public engagement. This study emphasizes the importance of fairness and transparency in employment, corporate social responsibility activities, and public engagement, as well as the necessity of communicating and mitigating environmental and social risks both before and during the implementation of geothermal energy projects. It recommends that policymakers establish clear, transparent guidelines for public engagement and strengthen legal frameworks regarding land ownership and resettlement to reduce conflicts. Additionally, corporates should focus on enhancing transparency in corporate practices and ensuring procedural fairness to foster trust with local communities and leaders.